2022
DOI: 10.3389/fgene.2022.900357
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic and Phylogenetic Analysis of Chloroplast Genomes of Hawthorn (Crataegus spp.) in Southwest China

Abstract: The hawthorns (Crataegus spp.) are widely distributed and famous for their edible and medicinal values. There are ∼18 species and seven varieties of hawthorn in China distributed throughout the country. We now report the chloroplast genome sequences from C. scabrifolia, C. chungtienensis and C. oresbia, from the southwest of China and compare them with the previously released six species in Crataegus and four species in Rosaceae. The chloroplast genome structure of Crataegus is typical and can be divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…We found that this divergent region of V. mongolicum existed in many plants such as Morella rubra (Liu et al, 2017), Angelica polymorpha (Park et al, 2019), Coffea arabica (Samson et al, 2007), Impatiens (Luo et al, 2021), Mangifera (Niu et al, 2021), Aconitum (Park et al, 2017), Arnebia and Lithospermum (Park et al, 2020), Justicia (Zhou et al, 2021), and Populus (Zong et al, 2019), indicating the variation of ycf4-cemA gene region is a common event in plants. The divergent sequence of ndhF gene fragment appeared in medicinal plants of Dolomiaea (Shen et al, 2020), Rheum (Xin et al, 2022), and Crataegus (Wu et al, 2022), supporting our findings of a highly differentiated ndhF segment of the photosynthetic system gene in the cp genomes of Vincetoxicum. In this study, two highly variable regions of ndhF-rpl32 and rpl32-ccsA were found in the cp genome of V. mongolicum, which were also marked and identified as the DNA barcodes in plants such as Pterocarpus (Jiao et al, 2019), Stipa (Krawczyk et al, 2018), Ardisia (Xie et al, 2021), and Alpinia (Li et al, 2020a).…”
Section: Vincetoxicum Mongolicumsupporting
confidence: 87%
See 1 more Smart Citation
“…We found that this divergent region of V. mongolicum existed in many plants such as Morella rubra (Liu et al, 2017), Angelica polymorpha (Park et al, 2019), Coffea arabica (Samson et al, 2007), Impatiens (Luo et al, 2021), Mangifera (Niu et al, 2021), Aconitum (Park et al, 2017), Arnebia and Lithospermum (Park et al, 2020), Justicia (Zhou et al, 2021), and Populus (Zong et al, 2019), indicating the variation of ycf4-cemA gene region is a common event in plants. The divergent sequence of ndhF gene fragment appeared in medicinal plants of Dolomiaea (Shen et al, 2020), Rheum (Xin et al, 2022), and Crataegus (Wu et al, 2022), supporting our findings of a highly differentiated ndhF segment of the photosynthetic system gene in the cp genomes of Vincetoxicum. In this study, two highly variable regions of ndhF-rpl32 and rpl32-ccsA were found in the cp genome of V. mongolicum, which were also marked and identified as the DNA barcodes in plants such as Pterocarpus (Jiao et al, 2019), Stipa (Krawczyk et al, 2018), Ardisia (Xie et al, 2021), and Alpinia (Li et al, 2020a).…”
Section: Vincetoxicum Mongolicumsupporting
confidence: 87%
“…The results showed that the rps16-psbK gene segment was significantly different in all the complete cp genomes of the seven species of Vincetoxicum, which could be used as a key genetic indicator for their phylogenetic classification. The rps16-psbK gene fragment was found to be a hypervariable region in the cp genomes of almond (Wang et al, 2020) and Crataegus (Wu et al, 2022) species and could be used as a divergent region in the genus of Vincetoxicum in this study.…”
Section: Vincetoxicum Mongolicummentioning
confidence: 82%
“…The GC content varied from 38.2 to 38.3% and the genome size varied from 153,959 to 154,932 bp, indicating the existence of genetic diversity. Compared to other medicinal plants, such as Artemisia (Pi = 0.0024), Atractylodes (Pi = 0.001), Crataegus (Pi = 0.00175) and Ligusticum (Pi = 0.002), Coptis (Pi = 0.0067) is a medicinal genus with relatively high genetic diversity ( Kim et al., 2020 ; Wang Y. et al., 2021 ; Wu et al., 2022 ; Wei et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%